The Truth app - Heath, Jack, 1986- (Liars, 2020)
High schooler Jarli Durras becomes an overnight celebrity after creating an app that can tell when a person is lying, but his fame soon turns dangerous when a secret network of criminals adds Jarli to its hit list.